(untitled) (Vallis Aurea, 2024)
The paper aims to investigate various factors influencing tourists’ attitudes i.e., satisfaction with both the accommodation units and the catering offer, the professionalism and hospitality of the tourism staff, a sense of security, lack of tourism offer, but also their motives, accommodation and arrival arrangements, their spending budgets etc. An online questionnaire was adopted using a convenience and snowball sampling techniques. The distinctiveness of the Eastern part of the Istria County also lies in the fact that, as shown by this research, visitors have a tendency to return, which indicates satisfaction with previous experiences and which is reflected by a large percentage of independent organization of arrivals, both thanks to the proximity of outbound travel markets, and the high degree of security that visitors have recognized in the destination. Given the fact that previously mentioned area is a less populated and not so touristically prominent part of the largest Croatian peninsula compared to its western part, tourists’ attitudes toward the tourism offer have not been an object of many studies.